Mapping the primary outcomes reported in cochrane systematic reviews regarding stroke with the international Classification of Functioning, Disability and Health domains current trend and future recommendations - Julia, Patrick Engkasan; Aishah, Ahmad Fauzi; Sakinah, Sabirin; Chai, Chau Chung; Izwan Zuhrin, Abdul Malek; Sara, Liguori; Antimo, Moretti (Edizioni Minerva Medica S.p.A., 2019)
BACKGROUND: The International Classification of Functioning, Disability and Health (ICF) serves as a framework for defining and categorizing health and functioning. ICF could be used to classify research outcomes in a systematic manner. AIM: The aim of this study was to classify the primary outcomes used in Cochrane Systematic Reviews (CSRs) into the ICF domains of functioning; to describe the differences in primary outcomes in reviews related to rehabilitation intervention and non-rehabilitation intervention; and to describe the trend of outcome selections according year of publication. DESIGN: Methodological paper. POPULATION: Adult stroke population. METHODS: We analyzed the primary outcomes used in the CSRs published by the Cochrane Stroke Review Group up to December 2017. The primary outcomes were extracted and classified into the ICF domains of functioning (body functions, body structures and activity and participation). RESULTS: One hundred and seventy-four papers with 216 primary outcomes were included in this analysis. Less than half (102/216, 47.2%) of the outcomes could be classified into the ICF domains of functioning. For the outcomes that could be classified into the ICF domains, the majority (72/102, 70.5%) were in the activity and participation domain, followed by body functions (26/102, 25.5%) and body structures (4/102, 4.0%). Of the outcomes that could not be classified into the ICF domains (N.=114), death (81/114, 71.1%) and recurrent stroke (21/114,18.4%) formed the majority of the outcome. There were 75 CSRs on rehabilitation related interventions; the majority of the outcomes (75/97, 77.3%) used in rehabilitation related CSRs could be classified into the ICF framework with more than half (49/75, 65.3%) in the activity and participation domain. CONCLUSIONS: The majority of the primary outcomes selected by the Cochrane Stroke Review Group in their CSRs could not be classified into the ICF domains of functioning. Death and recurrence of vascular events remains the major outcome of interest. In rehabilitation related interventions, activity and participation domain is the functioning domain most commonly used.